The ecological succession and characteristics in small Finnish polyhumic reservoirs - Koskenniemi, Esa (1995)
In this work, the ecological succession and characteristics of Finnish reservoirs were studied. Bottom characteristics, water quality, macrozoobenthos and fish communities were studied in over ten reservoirs, whereas succession studies were concentrated on a typical Finnish reservoir, Lake Kyrkösjärvi (A=6.4 km2 at summer HW, zₘₑₐₙ=2.5 m), since its filling up in 1981. Special attention was paid to macrozoobenthos, which – due to specific reservoir conditions - called for extraordinary work in sampling and taxonomic analysis. Most of the Finnish reservoirs are constructed since the 60's in Western Finland for flood control and hydro power purposes. Their bottom areas are nearly totally terrestrial consisting of woodland and peatland, and the winter draw-down affects drying and/or freezing of the bottom. The woodland shorelines erode rapidly in reservoirs, but elsewhere the bottoms remain rather unchanged, due to low decomposition and sedimentation rates. In winter, severe oxygen depletion is detected in these polyhumic waters, where seasonal variations in water quality exceed well the long-term changes. Vegetation and macrozoobenthos colonization is a rapid process, favored by species with high dispersal activity and rapid growth rate. In succession, the changes in species composition of biotic communities are clear and very few dominant species indicate different phases. In the most acidic reservoirs (pH 5 - 5.5) the overgrowth of water mosses is often observed, and many zoobenthic groups are poorly represented. The descriptive models of ecological succession in reservoirs fit Finnish conditions rather well, and general succession theory contributes to the understanding of these processes. Despite the differences in water level regime and bottom characteristics, the biota of Finnish reservoirs are quite similar to those of natural forest lakes. The reservoir zoobenthos is characterized by a dominance of insects and community composition places reservoirs as somewhat intermediate between pools and lakes. Harsh environmental conditions restrict the diversity of biotic communities. In the most acidic reservoirs, fisheries management possibilities are very limited.